High-elasticity textile fiber and preparation process thereof

By using specific polyols and isocyanate polymerization in fiber materials, combined with chain extension reaction and the application of modified diatomaceous earth, the shortcomings of fiber materials in terms of heat resistance, mechanical properties and antibacterial properties are solved, and high elasticity and resistance are achieved. Heat and antibacterial textile fibers.

CN119411249AActive Publication Date: 2025-02-11GUANGZHOU XIAOYANZHIJIA BABY & CHILD PRODUCTS CO LTD

Patent Information

Application Number
CN202411441859.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-11
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

Existing fiber materials have shortcomings in terms of heat resistance, mechanical properties and antibacterial properties, especially the nylon fiber has poor hygroscopicity and moisture rebate rate, and poor antibacterial properties, which limits its application range.

Method used

By using end-hydroxyl polydimethylsiloxane as polyol, the molar ratio of polyurethane prepolymer and polyamide prepolymer is controlled, the polymerization of linear hexamethylene diisocyanate and soft-segment polyol is combined, and 2 ,2-dihydroxymethylpropionic acid undergoes chain extension reaction to produce textile fibers with high elasticity and heat resistance. At the same time, diatomaceous earth is modified by 10% quaternary ammonium salt compound to enhance the antibacterial properties of the fiber.

Benefits of technology

The high elasticity, heat resistance and excellent antibacterial properties of textile fibers have been achieved, which are manifested as significantly improving the break strength and elongation of break of the fibers, improving the heat resistance, suitable hygroscopicity and moisture rebate, and golden color The inhibition rates of Staphylococcus and E. coli reached 99.6% and 99.5%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119411249A_ABST
    Figure CN119411249A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of synthetic fibers, in particular to a high-elasticity textile fiber and a preparation process thereof. The high-elasticity textile fiber is prepared from the polyurethane-polyamide elastomer and the modified diatomite master batch through melt spinning, drafting and winding. According to the invention, hydroxyl-terminated polydimethylsiloxane is used as polyol, and the molar ratio of the polyurethane prepolymer to the polyamide prepolymer is controlled, so that the prepared polyamide-polyurethane elastomer slice has good heat resistance; the molar ratio of isocyanate to polyol and the molar mass ratio of caprolactam to adipic acid are controlled, so that the prepared textile fiber is excellent in mechanical property; 2, 2-dimethylolpropionic acid is used for a chain extension reaction, the molar ratio is controlled, the moisture regain of the prepared textile fiber is 8.58%, and the moisture absorption is high; the diatomite is modified by the quaternary ammonium salt compound, and the addition proportion is adjusted, so that the prepared spinning fiber has good antibacterial performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of synthetic fibers, in particular to a high-elastic textile fiber and a preparation process thereof. Background Art

[0002] With the progress of society, the development of science and technology and the improvement of living standards, people's clothing consumption concepts and market demands have changed significantly. The requirements for fibers and textiles are not only durable and beautiful, but also pursue the comfort, health, safety, protection and environmental protection of textiles. Among the many functional textile fiber varieties, elastic fiber can give the human body a good sense of contact, and plays an irreplaceable role in the comfort, fluffy and warm aspects of clothing. Therefore, it occupies a solid position in the textile industry, and giving textile fabrics a certain degree of elasticity has become an inevitable development trend of clothing textiles. Elastic fibers are mainly divided into polyester fibers, composite elastic fibers, polyolefin elastic fibers and nylon fibers according to their varieties and compositions.

[0003] As the world's first commercial synthetic fiber product, nylon fiber has the advantages of high strength, good heat resistance, high wear resistance, etc., and is widely used in clothing, textiles, buckles, and connecting belts. However, with the development of technology, nylon fiber itself has problems with poor moisture absorption and moisture regain, which affects the wearing comfort of clothing and apparel products; and nylon fiber has poor antibacterial properties and is prone to breeding bacteria, thus limiting the scope of application of nylon fiber.

[0004] Patent CN202010881729.X reports a polyurethane-nylon 6 block copolymer, a preparation method thereof, and a polyurethane-nylon 6 elastic fiber. The polyurethane-nylon 6 block copolymer is an ABA-type block copolymer. The copolymer is melt-spun to obtain a high-strength, high-resilience polyurethane nylon 6 elastic fiber. However, the problem of poor hygroscopicity and antibacterial properties of nylon fibers is not solved.

[0005] CN201410799837.7 discloses a melt reaction preparation method for nylon polyurethane elastomer, which mainly comprises firstly uniformly blending amino-terminated nylon, isocyanate-terminated polyurethane, heat stabilizer, light stabilizer and water stabilizer, and then performing melt reaction through a twin-screw or internal mixer to obtain a nylon polyurethane elastomer. This method directly melt-blends polyurethane and nylon in an extruder, and the efficiency of the copolymerization reaction is low, and the obtained nylon polyurethane elastomer has a tensile strength of less than 30 MPa, which is much lower than the tensile strength of practical polyamide fiber or spandex, and has poor mechanical properties.

[0006] The elastic effect of the fabric mainly depends on the characteristics of the fiber used. Currently, the most commonly used elastic fiber on the market is polyurethane fiber, but the strength of polyurethane fiber is slightly insufficient, and its oxidation resistance and heat resistance are poor. The washing process must be kept at low temperature and gentle mode, otherwise shrinkage or rupture will occur. In addition, the antibacterial and deodorizing effects of polyurethane fiber are not very good.

[0007] Patent CN202110724023.7 reports spandex that is easily dyed with reactive dyes and its preparation method. A dihydroxy polymer containing a tertiary amine group is introduced into the soft segment of the polyurethane elastic fiber, and an organic compound containing lithium is added to the polyurethane elastic fiber spinning aid to improve the dyeing rate of the reactive dye on the polyurethane elastic fiber. However, the elastic properties of the polyurethane fiber prepared by this method change significantly, and the added lithium-based compound will accelerate the deterioration of the polyurethane elasticity.

[0008] In summary, polyurethane fibers are prone to poor heat resistance and low antibacterial effect; nylon fibers have poor moisture absorption and regain, and insufficient antibacterial properties, which limit the application scope of nylon fibers; a series of process improvements have been made to the fibers in the prior art, but there are still problems such as insufficient elasticity, poor heat resistance, and the need to improve mechanical properties.

[0009] Therefore, a high-elastic textile fiber and a preparation process thereof are proposed. Summary of the invention

[0010] The object of the present invention is to provide a high elastic textile fiber and a preparation process thereof. The invention adopts hydroxy-terminated polydimethylsiloxane as a polyol, controls the molar ratio of a polyurethane prepolymer to a polyamide prepolymer to be 1.3:1, and the obtained polyamide-polyurethane elastomer slice has a mass loss of 5% at a temperature of 358°C and a mass loss of 95% at a temperature of 484°C, and the heat resistance is improved. The linear hexamethylene diisocyanate is polymerized with a soft segment polyol, the molar ratio of isocyanate to polyol is controlled, and the molar mass ratio of caprolactam to adipic acid in the polyamide prepolymer is adjusted at the same time, and the obtained textile fiber is obtained. The breaking strength of the woven fiber is 7.2cN / dtex, and the elongation at break is 85.4%; 2,2-dihydroxymethylpropionic acid is used to carry out chain extension reaction on the polyurethane reaction system, and the molar ratio of the polyurethane reaction system to the chain extender is controlled to be 1:1.5. When the chain extension reaction temperature is 50°C, the moisture regain of the obtained textile fiber is 8.58%, and the hygroscopicity is strong; diatomaceous earth is modified by 10% quaternary ammonium salt compounds, and the addition amount of modified diatomaceous earth is 15%. The inhibition rate of the obtained spinning fiber on Staphylococcus aureus is 99.6%, and the inhibition rate on Escherichia coli is 99.5%, and the antibacterial property is excellent.

[0011] To achieve the above object, the present invention provides the following technical solutions:

[0012] A preparation process of a high-elastic textile fiber, characterized in that the preparation process of the high-elastic textile fiber comprises the following steps:

[0013] Dissolve isocyanate and polyol in DMF, heat to 50°C, add dibutyltin dilaurate and react for 3h, then add chain extender and react at 50-100°C for 2h to obtain polyurethane prepolymer;

[0014] Put caprolactam, deionized water and adipic acid into a reactor, react at 230°C and 100 rpm for 2 hours, and remove water to obtain a polyamide prepolymer;

[0015] The diatomite was added into a sodium hydroxide solution, a modifier was added, the mixture was stirred at 200 r / min for 2 h, centrifuged, sieved, and vacuum dried at 100° C. for 2 h to obtain a modified diatomite masterbatch;

[0016] The polyurethane prepolymer is added to the polyamide prepolymer, stirred at 60-100° C. and 300 rpm for 3 h, washed with cold water, vacuum dried at 80° C. for 1 h, and sliced ​​to obtain polyamide-polyurethane elastomer slices;

[0017] The polyamide-polyurethane elastomer slices and the modified diatomaceous earth masterbatch are vacuum dried at 115° C. and 100 Pa for 48 hours to obtain dry slices; the dry slices are added into a two-component composite melt low-speed spinning machine for melt spinning, heat drawing, and winding to obtain high-elastic textile fibers;

[0018] The mass ratio of the modified diatomite masterbatch to the polyamide-polyurethane elastomer slice is 1:5-10;

[0019] The molar ratio of the polyurethane prepolymer to the polyamide prepolymer is 1-1.5:1;

[0020] The molar ratio of the isocyanate to the polyol is 1-1.3:1;

[0021] The molar ratio of the caprolactam to the adipic acid is 3-10:1;

[0022] The process parameters of the heat drawing include: a drawing multiple of 1.5-4 times, a heat setting temperature of 80-120° C., and heat setting methods including pre-setting, mid-setting, and post-setting.

[0023] Preferably, the dried slices are dried to a moisture content of less than 30 ppm before spinning.

[0024] Preferably, the polyol is selected from one of polyether glycol, polypropylene glycol, polycaprolactone glycol, polytetramethylene glycol, and hydroxy-terminated polydimethylsiloxane.

[0025] Preferably, the isocyanate is selected from toluene diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, and terephthalylidene diisocyanate.

[0026] Preferably, the chain extender is selected from one of butanediol, 2,2-dimethylolpropionic acid, 1,6-hexanediol and trimethylolpropane.

[0027] Preferably, the modifier is selected from one of nano zinc oxide, nano silver oxide, and trimethylammonium chloride acetylhydrazine.

[0028] Preferably, the preparation of the polyurethane prepolymer comprises the following steps:

[0029] The isocyanate and the polyol are dried in a vacuum drying oven at 80° C. for 2 hours to obtain a dry raw material; the polyol and the isocyanate are added into a flask and dissolved in DMF to obtain a dissolving system; the dissolving system is heated to 50° C., and dibutyltin dilaurate is added and reacted for 3 hours to obtain a reaction system; a chain extender is added into the reaction system, and a chain extension reaction is carried out at 50-80° C. for 2 hours to obtain a polyurethane prepolymer.

[0030] Preferably, the preparation of the polyamide prepolymer comprises the following steps:

[0031] Caprolactam, deionized water and adipic acid were put into a reactor, the reactor was sealed with nitrogen, and the reaction was stirred at 100 rpm for 2 hours at 230° C. to obtain a reaction liquid; the reaction liquid was cooled and depressurized, and vacuumed for 5 minutes to remove moisture to obtain a polyamide prepolymer.

[0032] Preferably, the preparation of the modified diatomite masterbatch comprises the following steps:

[0033] Weigh diatomaceous earth and add it into a muffle furnace, calcine it at 450° C. for 2 h to obtain porous diatomaceous earth; add the porous diatomaceous earth into a ball mill for wet ultrafine grinding to make its average particle size reach the micron level to obtain ground diatomaceous earth; add the ground diatomaceous earth into 5 ml of sodium hydroxide solution, add a modifier, stir for 2 h at 200 r / min, centrifuge, sieve, and vacuum dry at 100° C. for 2 h to obtain modified diatomaceous earth masterbatch.

[0034] Preferably, during the preparation of the modified diatomite masterbatch, the modifier accounts for 5%-15% of the mass of the diatomite.

[0035] Preferably, the two-component composite melt low-speed spinning machine for preparing fiber filaments includes polyamide-polyurethane elastomer chips and modified diatomaceous earth masterbatch passing through a hopper, screw melting, metering pump, spinning assembly, wire drawing, oiling wheel, hot drawing, and winding.

[0036] Preferably, the operating parameters of the two-component composite melt low-speed spinning machine are: the screw section temperature is controlled at 280°C-290°C, the spinneret temperature is controlled at 240°C, the metering pump temperature is 260°C, and the pump pressure is 6MPa.

[0037] Preferably, the two-component composite melt low-speed spinning machine includes the fiber filaments sequentially entering an unwinding wheel, a low-speed drawing wheel, a shaping hot box, a high-speed drawing wheel, and a collecting wheel, and finally the fiber filaments are wound into a roll through a winding drum.

[0038] Preferably, the shaping method refers to the different positions of the shaping heat box during the stretching process, which are defined as front shaping, middle shaping and rear shaping according to the shaping box being located before the low-speed stretching wheel, between the low-speed stretching wheel and the high-speed stretching wheel, and after the high-speed stretching wheel.

[0039] A high-elastic textile fiber, characterized in that: the high-elastic textile fiber comprises the polyurethane prepolymer, the polyamide prepolymer, and the modified diatomaceous earth masterbatch; the high-elastic textile fiber is prepared by any one of the preparation methods described above; the polyamide-polyurethane elastomer slice in the high-elastic textile fiber has a T5% of 358°C and a T95% of 484°C; the high-elastic textile fiber has a breaking strength of 7.2 cN / dtex and an elongation at break of 85.4%; the elastic recovery rate of the high-elastic spun fiber at a fixed elongation of 10% is 99.6%; the moisture regain of the high-elastic spun fiber at constant temperature and humidity for 48 hours is 8.58%; the high-elastic spun fiber has a Staphylococcus aureus inhibition rate of 99.6% and an Escherichia coli inhibition rate of 99.5%.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] 1. The present invention utilizes terminal hydroxyl polydimethylsiloxane to polymerize with isocyanate, and the polyurethane prepolymer obtained by the action of a chain extender and the polyamide prepolymer to undergo a condensation reaction to obtain a polyamide-polyurethane elastomer. The terminal hydroxyl polydimethylsiloxane molecule contains Si-O bonds, and the increase in bond energy increases the overall heat resistance of the elastomer. At the same time, the main chain of the siloxane molecule increases the interchain hydrogen bond force, the interaction between molecular chain segments is enhanced, and the heat resistance is enhanced. The molar ratio of the polyurethane prepolymer to the polyamide prepolymer is controlled to be 1.3:1. The temperature of the obtained polyamide-polyurethane elastomer slice is 358° C. when the mass loss is 5%, and the temperature is 457° C. when the mass loss is 95%, showing significantly improved heat resistance.

[0042] 2. The present invention uses linear hexamethylene diisocyanate and soft segment polyol for polymerization, controls the molar ratio of isocyanate to polyol, and adjusts the molar mass ratio of caprolactam and adipic acid in the polyamide prepolymer. The use of long-chain isocyanate can effectively reduce the force, and the applied stress can be dispersed in the fatty straight chain. At the same time, the amount of caprolactam is increased, the number of amino groups and amide bonds in the molecule increases, the hydrogen bond force is enhanced, and the intermolecular attraction is increased. The obtained textile fiber has a breaking strength of 7.2 cN / dtex and an elongation at break of 85.4%.

[0043] 3. The present invention adopts a two-component composite melt low-speed spinning machine to melt-spin polyamide-polyurethane elastomer slices and modified diatomite masterbatch, and explores the mechanical properties of textile fibers through the drafting process. Since the number of microcrystals formed by the primary fibers extruded at low speed is very small, the corresponding physical cross-linking points are small, and irreversible deformation is easily produced, and the elastic recovery rate is low. The elastic recovery rate of textile fibers is improved through the drafting process; through experimental exploration, the drafting multiple is 4 times, and the elastic recovery rate of the spun fibers obtained at a fixed elongation of 10% is 99.6% at a medium setting at 100°C.

[0044] 4. The present invention utilizes 2,2-dimethylol propionic acid to carry out chain extension reaction on a polyurethane reaction system to obtain a polyurethane prepolymer, and obtains a textile fiber by condensation polymerization reaction with a polyamide prepolymer and melt drawing. The -COOH group is introduced into a chain extender, and the -COOH free on the surface of the textile fiber is combined with water molecules due to hydrogen bonding, thereby improving the hygroscopicity of the textile fiber. At the same time, after the chain extender chain segment is introduced into the main chain, the regularity of the molecular chain is destroyed, the hydrogen bond density between the molecular chains is reduced, the crystallinity of the fiber is reduced, and the moisture regain of the fiber is increased. When the molar ratio of the polyurethane reaction system to the chain extender is controlled to be 1:1.5 and the chain extension reaction temperature is 50°C, the moisture regain of the obtained textile fiber is 8.58%, showing significantly improved hygroscopicity.

[0045] 5. The present invention utilizes modified diatomite and polyamide-polyurethane elastomer slices to melt-draw to obtain textile fibers, enhances the antibacterial properties of textile fibers, controls the spinning speed and the amount of modified diatomite, stabilizes the spinning, and obtains spun fibers. Quaternary ammonium salt compounds can be filled in the pores of diatomite, and the free polar groups can produce hydrogen bonds with the elastomer slices, increase compatibility, and cooperate with diatomite to improve the antibacterial properties of the fibers; adding a modifier with a mass ratio of 10%, and the amount of modified diatomite added is 15%, the obtained spun fibers have an inhibition rate of 99.6% on Staphylococcus aureus and an inhibition rate of 99.5% on Escherichia coli, showing significantly improved antibacterial properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 Thermogravimetric curves of Example 5 and Comparative Examples 1-2;

[0047] Figure 2 This is a graph showing the change in elastic recovery rate under a condition of 5%-30% elongation for Examples 25-29. DETAILED DESCRIPTION

[0048] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0049] See also Figure 1 to Figure 2 The present invention provides a high elastic textile fiber and a preparation process thereof, and the technical scheme is as follows:

[0050] Examples 1-13

[0051] Dry toluene diisocyanate and polyol in a vacuum drying oven at 80°C for 2 hours to obtain a dry raw material; add the dihydroxy polydimethylsiloxane and the toluene diisocyanate into a four-necked flask and dissolve them in 2 ml of DMF to obtain a dissolving system; protect the dissolving system with nitrogen, heat it to 50°C, add 1% of a catalyst dibutyltin dilaurate and react for 3 hours to obtain a reaction system; add a chain extender to the reaction system, keep it at 50°C for a chain extension reaction for 2 hours to obtain a polyurethane prepolymer.

[0052] 24 mol of caprolactam, deionized water (accounting for 3% of the mass of caprolactam) and 3 mol of adipic acid were put into a 10L nitrogen exchange reactor, the reactor was sealed, and the reaction was stirred at 100 rpm for 2 hours at 230°C to obtain a reaction liquid; the reaction liquid was cooled and reduced in pressure, and vacuumed for 5 minutes to remove moisture to obtain a polyamide prepolymer.

[0053] The polyurethane prepolymer is added to the polyamide prepolymer, and the reaction is carried out under vacuum conditions at 60-100° C. and 300 rpm for 3 hours to obtain a reactant; when the melt in the reactant is transparent and has few bubbles, vacuum is applied for 10 minutes, the stirrer is turned off, the reactant is washed with supercooled water, vacuum dried at 80° C. for 1 hour, and sliced ​​to obtain polyamide-polyurethane elastomer slices.

[0054] Weigh diatomite and add it into a muffle furnace, calcine it at 450° C. for 2 h to obtain porous diatomite; add the porous diatomite into a ball mill for wet ultrafine grinding to make its average particle size reach the micron level to obtain ground diatomite; add 10 g of the ground diatomite into 5 ml of sodium hydroxide solution, add 1 g of nano zinc oxide, stir at 200 r / min for 2 h, centrifuge and filter, and vacuum dry at 100° C. for 2 h to obtain a modified diatomite masterbatch.

[0055] Preparation of highly elastic textile fibers:

[0056] 100g of the polyamide-polyurethane elastomer slices and 20g of the modified diatomite masterbatch were placed in a vacuum drying oven for drying at a temperature of 115°C, a vacuum degree of 100Pa, and a drying time of 48h to obtain dried slices; the dried slices were added to a two-component composite melt low-speed spinning machine for melt spinning and winding, and the fibers were heat-stretched to obtain high-elastic textile fibers. The spinneret used had a specification of 0.28*0.84mm and 36 holes; the spinning speed was 980m / min. The differences between Examples 1-13 are shown in Table 1.

[0057] Table 1 Differences in the amount of components used in Examples 1-13

[0058] Example Polyol Type <![CDATA[n (聚氨酯) :n (聚酰胺) ]]> Reaction temperature / ℃ Example 1 Polyether diol 1.3:1 80 Example 2 Polypropylene glycol 1.3:1 80 Example 3 Polycaprolactone diol 1.3:1 80 Example 4 Polytetrahydrofurandiol 1.3:1 80 Example 5 Hydroxyl-terminated polydimethylsiloxane 1.3:1 80 Example 6 Hydroxyl-terminated polydimethylsiloxane 1.3:1 60 Example 7 Hydroxyl-terminated polydimethylsiloxane 1.3:1 70 Example 8 Hydroxyl-terminated polydimethylsiloxane 1.3:1 90 Example 9 Hydroxyl-terminated polydimethylsiloxane 1.3:1 100 Example 10 Hydroxyl-terminated polydimethylsiloxane 1:1 80 Embodiment 11 Hydroxyl-terminated polydimethylsiloxane 1.2:1 80 Example 12 Hydroxyl-terminated polydimethylsiloxane 1.4:1 80 Example 13 Hydroxyl-terminated polydimethylsiloxane 1.5:1 80

[0059] Comparative Example 1 refers to the preparation method and parameter conditions of Example 1, except that no polyamide prepolymer is added and only polyurethane prepolymer is used as the spinning sheet body.

[0060] Comparative Example 2 refers to the preparation method and parameter conditions of Example 1, except that no polyurethane prepolymer is added and only polyamide prepolymer is used as the spinning sheet body.

[0061] Example 14 Heat resistance test

[0062] The polyamide-polyurethane elastomers prepared in Examples 1-13 and Comparative Examples 1-2 were tested for melting and crystallization properties using a differential calorimeter (DSC-822). Before the test, the elastomer slices were vacuum dried at 105°C for 12 hours and then weighed to 10 mg. The slices were placed in a crucible for sample preparation. Under a nitrogen atmosphere, the heating and cooling rate was maintained at 10°C / min. The test temperature was increased from 30°C to 280°C, maintained for three minutes, and then decreased from 280°C to 30°C. The melting temperature was recorded. The experimental results are shown in Table 2.

[0063] The polyamide-polyurethane elastomers prepared in Examples 1-13 and Comparative Examples 1-2 were subjected to a thermal stability test using a thermogravimetric analyzer (TGA8000). After drying at 80°C in vacuum for 12 hours, 10 mg was weighed and sampled in a crucible. The thermal stability test was performed at a heating rate of 20°C / min from 30°C to 600°C in a nitrogen atmosphere with a flow rate of 50 ml / min. The thermogravimetric curves of Example 5 and Comparative Examples 1-2 are shown in FIG. Figure 1 As shown, T 5% , T 95% . T 5% is the temperature corresponding to 5% mass loss, T 95% is the temperature corresponding to 95% mass loss. The experimental results are shown in Table 2.

[0064] Table 2 Heat resistance test results of Examples 1-13 and Comparative Examples 1-2

[0065]

[0066] Through Table 1, Figure 1 The results show that in Comparative Examples 1-2, only polyamide prepolymer or polyurethane prepolymer is used as the elastomer, which can be spun into fibers, but the heat resistance of the elastomer shows a significant decrease compared with Example 5; the results of Comparative Examples 1-5 show that the use of different types of polyols affects the overall heat resistance of the elastomer. The use of ester bonds and ether chains introduced destroys the regularity of local molecular chains, further reduces the hydrogen bond density between the main chains, reduces the interaction force between molecular chains, reduces crystallization, makes molecular segments easier to move, and reduces heat resistance. Since the terminal hydroxyl polydimethylsiloxane molecules contain Si-O bonds, the bond energy increases, which increases the overall heat resistance of the elastomer. At the same time, the main chain of the siloxane molecule increases the hydrogen bond force between chains, the interaction between molecular segments is enhanced, and the heat resistance is increased; the results of Comparative Examples 1 and Examples 6-9 show that with the increase of the reaction temperature, the melting temperature and decomposition temperature of the elastomer gradually increase. Due to the increase in temperature, the free -NCO groups in the system move. Increase, the contact opportunity with the polar groups on the main chain increases, and the interaction force between the molecular chains is increased. However, with the increase of temperature, the cross-linking points generated increase, the viscosity of the elastomer increases, and spinning cannot be performed during the spinning process, affecting the processing performance; Comparing the results of Example 5 and Examples 10-13, it can be seen that with the increase of the molar ratio of the polyurethane prepolymer and the polyamide prepolymer, the melting temperature of the elastomer gradually decreases. Because at the same content, the larger the molecular weight of the polyurethane, the fewer the number of polyamide segments, and the less restriction of the polyamide segments on the polyurethane segments, and the thermal properties of the polyamide prepolymer are related to the molar ratio of the amide group to the methylene group in the main chain, the molecular weight of the polyurethane segment increases, and the ester bond content in the system increases accordingly. At the same time, the polar groups contained in the polyurethane further increase the intermolecular force, the regularity between the molecular chains decreases, the melting temperature of the elastomer decreases, and the heat resistance decreases. The increase in the amount of polyurethane reduces the viscosity of the system, and the later spinning is difficult; Comprehensive Table 2, Figure 1 The results show that when the polyurethane prepolymer is prepared using terminal hydroxyl polydimethylsiloxane as the polyol, and n(polyurethane):n(polyamide)=1.3:1, the temperature of the obtained polyamide-polyurethane elastomer slices is 358°C when the mass loss is 5%, and the temperature is 484°C when the mass loss is 95%.

[0067] Examples 15-23 refer to the preparation method and parameter conditions of Example 5, and the differences are shown in Table 3.

[0068] Comparative Example 3 refers to the preparation method and parameter conditions of Example 5, except that no polyamide prepolymer is added and only polyurethane prepolymer is used as the spinning sheet body.

[0069] Comparative Example 4 refers to the preparation method and parameter conditions of Example 5, except that no polyurethane prepolymer is added and only polyamide prepolymer is used as the spinning sheet body.

[0070] Example 24 Tensile Properties Test

[0071] The tensile properties of the fibers obtained in Examples 14-23 and Comparative Examples 3-4 were tested using a YG020B electronic single yarn strength tester produced by Changzhou Bafang Lisi Textile Instrument Co., Ltd. The clamping distance was 100 mm, the pre-tension was 0.05 cN / dtex, and the tensile speed was 500 mm / min. The test results are shown in Table 3.

[0072] Table 3 Tensile performance test of Examples 15-23 and Comparative Examples 3-4

[0073]

[0074]

[0075] From the results in Table 3, it can be seen that the breaking strength and breaking elongation of the spun fibers made by using only polyamide prepolymer or polyurethane prepolymer as elastomer in Comparative Examples 3-4 are significantly lower than those in Examples 15-23, and the mechanical properties are significantly reduced; from the results of Comparative Examples 15-18, it can be seen that the spun fibers finally made by using polyurethane prepolymer made from hexamethylene diisocyanate have significantly improved breaking elongation and breaking strength, because the use of long-chain isocyanates can effectively reduce the force, and the applied stress can be dispersed in the fatty straight chain, so that the breaking strength of the spinning material is increased, and at the same time, the dispersed force can improve the ductility of the spinning, and then improve the breaking elongation; aromatic isocyanates and alicyclic isocyanates effectively increase the strength of the elastomer due to their cyclic rigid structure, but due to the conjugation effect, the applied external force further enhances the intermolecular force in the structural system , resulting in a decrease in the breaking strength of spinning; it can be seen from the results of Example 15 and Examples 18-19 that with the increase in the molar ratio of isocyanate and polyol, the elongation at break and the breaking strength of spinning tend to remain unchanged; Comparative Example 15 and Examples 20-23, with the increase in the molar amount of caprolactam, the soft segment structure in the system decreases, the dispersion of the force weakens, and the breaking strength of the spinning material gradually decreases. Due to the increase in the amount of caprolactam, the intramolecular hydrogen bond force is enhanced, the intermolecular attraction increases, and the elongation at break increases; In summary, when hexamethylene diisocyanate is used to prepare a polyurethane prepolymer, and n(isocyanate):n(polyol)=1.2:1 and n(caprolactam):n(adipic acid)=8:1 are maintained, the obtained textile fiber has a breaking strength of 7.2 cN / dtex and an elongation at break of 85.4%, which has significantly improved mechanical properties.

[0076] Examples 25-35

[0077] 3.6 mol of hexamethylene diisocyanate and 3 mol of terminal hydroxyl polydimethylsiloxane are dried in a vacuum drying oven at 80°C for 2 hours to obtain a dry raw material; the dihydroxy polydimethylsiloxane and the hexamethylene diisocyanate are added into a four-necked flask and dissolved in 2 ml of DMF to obtain a dissolving system; the dissolving system is protected by nitrogen, the temperature is raised to 50°C, 0.036 mol of dibutyltin dilaurate is added and reacted for 3 hours to obtain a reaction system; a chain extender is added to the reaction system, and the system is kept at 50°C for chain extension reaction for 2 hours to obtain a polyurethane prepolymer.

[0078] 24 mol of caprolactam, deionized water (accounting for 3% of the mass of caprolactam) and 3 mol of adipic acid were put into a 10L nitrogen exchange reactor, the reactor was sealed, and the reaction was stirred at 100 rpm for 2 hours at 230°C to obtain a reaction liquid; the reaction liquid was cooled and reduced in pressure, and vacuumed for 5 minutes to remove moisture to obtain a polyamide prepolymer.

[0079] 1.3 mol of the polyurethane prepolymer is added to 1 mol of the polyamide prepolymer, and the reaction is continued under vacuum conditions at 60-100° C. and 300 rpm for 3 hours to obtain a reactant; when the melt in the reactant is transparent and has few bubbles, vacuum is applied for 10 minutes, the stirrer is turned off, the reactant is washed with supercooled water, vacuum dried at 80° C. for 1 hour, and sliced ​​to obtain polyamide-polyurethane elastomer slices.

[0080] Weigh diatomite and add it into a muffle furnace, calcine it at 450° C. for 2 h to obtain porous diatomite; add the porous diatomite into a ball mill for wet ultrafine grinding to make its average particle size reach the micron level to obtain ground diatomite; add 10 g of the ground diatomite into 5 ml of sodium hydroxide solution, add 1 g of nano zinc oxide, stir at 200 r / min for 2 h, centrifuge and filter, and vacuum dry at 100° C. for 2 h to obtain a modified diatomite masterbatch.

[0081] Preparation of highly elastic textile fibers:

[0082] The polyamide-polyurethane elastomer slices and the modified diatomaceous earth masterbatch are placed in a vacuum drying oven for drying at a temperature of 115° C., a vacuum degree of 100 Pa, and a drying time of 48 hours to obtain dried slices; the dried slices are added to a two-component composite melt low-speed spinning machine for melt spinning and winding, and the fibers are heat-stretched to obtain high-elastic textile fibers.

[0083] The differences in the hot stretching process parameters of Examples 25-35 are shown in Table 4.

[0084] Comparative Example 5 refers to the preparation method and parameter conditions of Example 29, except that no wire drawing treatment is performed.

[0085] Example 36 Elasticity Performance Measurement

[0086] The tensile test was conducted using a 5843 universal strength tester produced by INSTRON, USA, with a fixed elongation of 5%-30%, a clamping distance of 100mm, and a tensile speed of 500mm / min. The elastic recovery rate calculation formula is shown below.

[0087] Elastic recovery rate (%) = L0-L2 / L0×100%

[0088] Wherein: L0 is the set elongation value of the fiber; L2 is the elongation value corresponding to the fiber when it is stretched to the pre-tension after relaxation recovery. The elastic recovery rate when the set elongation is 10% is shown in Table 4; the elastic recovery rate change diagram of Examples 25-29 under the condition of set elongation of 5%-30% is shown in Figure 2 shown.

[0089] Table 4 Elastic recovery rate of Examples 25-35 and Comparative Example 5

[0090]

[0091] It can be seen from the results in Table 4 that the mechanical properties and elastic properties of the spinning material in Comparative Example 5 that are not subjected to the drawing treatment have obvious changes in the overall performance compared with those of Examples 25-35; it can be seen from the results of Examples 25-29 that with the increase of the drawing multiple, the macromolecular chains in the amorphous region are arranged more regularly along the axial direction, the degree of orientation increases, and the intermolecular force increases, so with the increase of the drawing multiple, the breaking strength increases and the breaking elongation decreases; since the number of crystallites formed by the primary fibers extruded at a low speed is extremely small, the corresponding physical cross-linking points are small, and irreversible deformation is easily produced, and the elastic recovery rate is low; and when the fibers are subjected to a certain drawing force, the hard segments in the polymer are oriented and crystallized, and the ability to resist deformation is enhanced, so the elastic recovery rate increases, but with the increase of the drawing multiple, the elastic recovery rate is not greatly affected; it can be seen from the results of Examples 25 and 30-31 that since the pre-setting is the stretching of the fibers after heat setting, heat setting can promote The degree of phase separation is improved, more physical cross-linking points are formed, and orientation and crystallization occur during the drawing process, and the degree of phase separation is further improved, the stability of the polyether elastic system is improved, the elastic recovery rate is increased, and the mid-setting and post-setting have little effect on the elastic recovery rate; however, post-setting is that the fiber is heat-set after cold drawing, and the macromolecular chains in the fiber are prone to dissociation, resulting in a decrease in breaking strength and an increase in breaking elongation; By comparing the results of Example 25 and Examples 32-35, it can be seen that as the heat setting temperature increases, the molecular movement inside the fiber intensifies, more macromolecular chains in the amorphous region are arranged in order, the force between the molecular chains is enhanced, and the molecular chains are not easy to slip, so the fiber breaking strength increases, the elongation at break decreases, and the elastic recovery rate shows a trend of increasing. However, when the reaction temperature rises to 110°C, the higher heat setting temperature increases the degree of fiber deorientation, weakens the degree of phase separation, and increases the irreversible plastic deformation of the fiber; by Figure 2 The results further verified that as the drafting ratio increased, the elastic recovery rate was not greatly affected, but as the fixed elongation increased, the elastic recovery rate of the spun fiber prepared in the example gradually decreased. When the fixed elongation changed to 30%, the elastic recovery rate of the spun fiber prepared in Example 29 was 85%. From the results in Table 4, it can be seen that the elastic recovery rate of the spun fiber prepared at a drafting ratio of 4 times and a fixed elongation of 10% at 100°C was 99.6%.

[0092] Examples 37-46 refer to the preparation method and parameter conditions of Example 29, the differences are shown in Table 5

[0093] Comparative Example 6 refers to the preparation method and parameter conditions of Example 29, except that no chain extender is added for chain extension treatment. Example 47 Hygroscopicity Test

[0094] Referring to GB / T 6503-2008 Test Method for Moisture Regain of Chemical Fibers, Examples 37-46 and Comparative Example 6 were placed in a 105°C blast oven for drying for 12 hours, and a fiber sample with a mass of m0 was weighed and humidified in a constant temperature and humidity chamber at 20°C and a relative humidity of 65% for 48 hours. The mass of the fiber after weighing was m1, and the average value was taken for three tests. The moisture regain of the fiber Mr was calculated according to the following formula, and the results are shown in Table 5. Mr = m1-m0 / m0×100%

[0095] Table 5 Hygroscopicity test of Examples 37-46 and Comparative Example 6

[0096]

[0097] From the results in Table 5, it can be seen that in Comparative Example 6, the polyurethane is chain extended without using a chain extender, and the moisture regain of the obtained textile fiber material is significantly reduced compared with Examples 37-46. The addition of a chain extender can effectively improve the moisture absorption and moisture regain properties of the fiber, and the fiber fabric with higher hygroscopicity is more comfortable to wear; from the results of Comparative Examples 37-40, it can be seen that the use of aliphatic diols and alicyclic alcohols as chain extenders can improve the moisture regain, but the moisture regain and hygroscopicity of polyols containing polar groups in the branched chains need to be improved. Due to the introduction of -COOH groups in the chain extenders, the -COOH free on the surface of the textile fibers and the water molecules are combined with each other due to hydrogen bonds, thereby improving the hygroscopicity of the textile fibers; from the results of Examples 37 and 41-43, it can be seen that with the increase of the chain extender content, the moisture regain of the textile fiber material gradually increases. This is due to the increase in crystallinity. Moisture absorption mainly occurs on the surface of the amorphous region and the crystalline region. The larger the amorphous region, the lower the crystallinity, the greater the moisture regain of the fiber, and the chain extender After the chain segment is introduced into the main chain, the regularity of the molecular chain is destroyed, the hydrogen bond density between the molecular chains is reduced, the crystallinity of the fiber is reduced, and the moisture regain is increased. As the chain extender is added in excess, the polar -COOH groups in the molecule increase, and the -COOH groups in the textile fiber are cross-linked with the -NCO groups, further affecting the overall mechanical properties of the fiber. By comparing the results of Example 37 and Examples 44-46, it can be seen that with the increase of the reaction temperature, the moisture regain first increases and then decreases. As the reaction temperature increases, the -COOH groups in the system are chemically cross-linked with the polar groups in the chain segments, the free -COOH groups on the fiber surface end are reduced, and the hydrogen bonding force on the water molecules is weakened, showing a significantly reduced moisture regain. From the results of Table 5, it can be seen that when 2,2-dihydroxymethylpropionic acid is used as the chain extender, the molar ratio of the reaction system to the chain extender is maintained at 1:1.5, and the chain extension reaction temperature is 50°C, the moisture regain of the obtained textile fiber is 8.58%, showing a significantly improved hygroscopic property.

[0098] Examples 47-53

[0099] 3.6 mol of hexamethylene diisocyanate and 3 mol of terminal hydroxyl polydimethylsiloxane are dried in a vacuum drying oven at 80°C for 2 hours to obtain a dry raw material; the dihydroxy polydimethylsiloxane and the hexamethylene diisocyanate are added into a four-necked flask and dissolved in 2 ml of DMF to obtain a dissolving system; the dissolving system is protected by nitrogen, the temperature is raised to 50°C, a catalyst dibutyltin dilaurate is added and reacted for 3 hours to obtain a reaction system; 9 mol of a chain extender is added to the reaction system, and the system is kept at 50°C for chain extension reaction for 2 hours to obtain a polyurethane prepolymer.

[0100] 24 mol of caprolactam, deionized water (accounting for 3% of the mass of caprolactam) and 3 mol of adipic acid were put into a 10L nitrogen exchange reactor, the reactor was sealed, and the reaction was stirred at 100 rpm for 2 hours at 230°C to obtain a reaction liquid; the reaction liquid was cooled and reduced in pressure, and vacuumed for 5 minutes to remove moisture to obtain a polyamide prepolymer.

[0101] 1.3 mol of the polyurethane prepolymer is added to 1 mol of the polyamide prepolymer, and the reaction is continued under vacuum conditions at 60-100° C. and 300 rpm for 3 hours to obtain a reactant; when the melt in the reactant is transparent and has few bubbles, vacuum is applied for 10 minutes, the stirrer is turned off, the reactant is washed with supercooled water, vacuum dried at 80° C. for 1 hour, and sliced ​​to obtain polyamide-polyurethane elastomer slices.

[0102] Weigh diatomaceous earth and add it into a muffle furnace, calcine it at 450° C. for 2 h to obtain porous diatomaceous earth; add the porous diatomaceous earth into a ball mill for wet ultrafine grinding to make its average particle size reach the micron level to obtain ground diatomaceous earth; add the ground diatomaceous earth into 5 ml of sodium hydroxide solution, add a modifier, stir for 2 h at 200 r / min, centrifuge, sieve, and vacuum dry at 100° C. for 2 h to obtain modified diatomaceous earth masterbatch.

[0103] Preparation of highly elastic textile fibers:

[0104] The polyamide-polyurethane elastomer slices and the modified diatomite masterbatch were placed in a vacuum drying oven for drying at a temperature of 115°C, a vacuum degree of 100 Pa, and a drying time of 48 hours to obtain dried slices; the dried slices were added to a two-component composite melt low-speed spinning machine for melt spinning and winding, and the fibers were heat-drawn to obtain high-elastic textile fibers. The relationship between the amount of modified diatomite added and the spinnability is shown in Table 6.

[0105] Table 6 Relationship between modified diatomite dosage and spinnability

[0106] Spinning speed m(elastomer slice): m(modified diatomaceous earth) Spinnability 1100 100:20 Difficulty in spinning 1050 100:20 Difficulty in spinning 1000 100:20 Severe decapitation 1000 100:15 Reduced end breakage and difficult winding 950 100:20 Increased number of decapitations 950 100:15 Spinning is stable and winding is normal 950 100:10 Winding is easy to break

[0107] Examples 47-53 were prepared and synthesized with reference to the spinning speed and addition ratio shown in Table 6, and the differences are shown in Table 7

[0108] Comparative Example 7 refers to the preparation method and parameter conditions of Example 47, except that no modifier is added to modify the diatomaceous earth.

[0109] Comparative Example 8 refers to the preparation method and parameter conditions of Example 47, except that modified diatomaceous earth is not added.

[0110] Example 54 Antibacterial Test

[0111] Staphylococcus aureus and Escherichia coli were selected as test strains, and the two bacteria were suspended in a phosphate buffer with a concentration of 100 μmol / L and pH=7 to prepare the required bacterial solution, and the bacterial solution was dropped on the textile fibers prepared in Examples 47-53 and Comparative Examples 7-8, respectively, and another piece of textile fiber was stacked in the form of a sandwich, and pressed with a sterile iron press for 10 minutes. The textile fiber subjected to the antibacterial test was exposed to sunlight for 30 minutes, and then placed in a centrifuge tube with a sterile sodium thiosulfate solution with a concentration of 0.03 mol / L and vibrated for 5 minutes, and then the above solution was continuously diluted with a phosphate buffer with a concentration of 100 μmol / L and pH=7, and the diluted solution was placed in a culture medium and cultured at a constant temperature of 37°C for 24 hours. Finally, the number of surviving bacterial colonies was counted and the antibacterial rate was calculated. The test results are shown in Table 7.

[0112] Table 7 Antibacterial performance test results of Examples 47-53 and Comparative Examples 7-8

[0113]

[0114]

[0115] From the results in Table 6, it can be seen that the amount of modified diatomite added directly affects the stability of the spinning state. With the increase of the spinning speed, the spinning stability is poor. Too fast spinning speed reduces the compatibility of the elastomer slices and diatomite, and the inorganic particles are free and affect the spinning stability. If the amount of modified diatomite added is too low, the function of the fiber cannot achieve the expected effect, and it is easy to break during the winding process. If too much is added, the viscosity of the spinning solution will be greatly reduced, resulting in an unstable spinning state, and it is easy to have undesirable phenomena such as broken wire and roller winding, which ultimately reduces the spinnability of the fiber. It is finally determined that when the addition ratio is 15% and the spinning speed is controlled at 950m / min, the breakage is less and the spinning state is controllable. From the results in Table 7, it can be seen that the spun fiber prepared in Comparative Example 8 without adding modified diatomite almost does not show antibacterial properties, while the spun fiber prepared by adding only diatomite in Comparative Example 7 has antibacterial properties. The antibacterial performance is significantly improved compared with Comparative Example 8, but there is still a significant gap relative to Examples 47-53. The modifier can be filled in the pore structure of diatomite and work together with the diatomite to exert antibacterial properties; the results of Examples 47-49 show that the use of nano-inorganic substances has significantly improved antibacterial properties relative to quaternary ammonium salt compounds. Since the nano-inorganic substances have poor compatibility with elastomers during the spinning process, and the quaternary ammonium salt compounds are filled in the pores, the free polar groups can produce hydrogen bonds with the elastomer slices, the compatibility is increased, and more excellent antibacterial properties are exhibited; the results of Examples 47 and 50-53 show that with the increase of the mass ratio of the modifier, the antibacterial properties of the textile fibers gradually increase and tend to stabilize. With the addition of quaternary ammonium salt compounds, the internal pores of the diatomite are filled, and the polar groups are free on the surface of the diatomite to exert antibacterial properties. From the results in Tables 6 and 7, it can be seen that the diatomaceous earth modified by 10% trimethylammonium chloride acetohydrazide and 15% modified diatomaceous earth added can produce a spun fiber with an inhibition rate of 99.6% against Staphylococcus aureus and 99.5% against Escherichia coli, showing significantly improved antibacterial properties.

[0116] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A process for preparing a highly elastic textile fiber, characterized in that: The preparation process of the highly elastic textile fiber comprises the following steps: Dissolve isocyanate and polyol in DMF, heat to 50°C, add dibutyltin dilaurate and react for 3h, add chain extender, and react at 50-100°C for 2h to obtain polyurethane prepolymer; Put caprolactam, deionized water and adipic acid into a reactor, react at 230°C and 100 rpm for 2 hours, and remove water to obtain a polyamide prepolymer; The diatomite was added into a sodium hydroxide solution, a modifier was added, the mixture was stirred at 200 r / min for 2 h, centrifuged, sieved, and vacuum dried at 100° C. for 2 h to obtain a modified diatomite masterbatch; The polyurethane prepolymer is added to the polyamide prepolymer, stirred at 60-100° C. and 300 rpm for 3 h, washed with cold water, vacuum dried at 80° C. for 1 h, and sliced ​​to obtain polyamide-polyurethane elastomer slices; The polyamide-polyurethane elastomer slices and the modified diatomaceous earth masterbatch are vacuum dried at 115° C. and 100 Pa for 48 hours to obtain dry slices; the dry slices are added into a two-component composite melt low-speed spinning machine for melt spinning, heat drawing, and winding to obtain high-elastic textile fibers; The mass ratio of the modified diatomite masterbatch to the polyamide-polyurethane elastomer slice is 1:5-10; The molar ratio of the polyurethane prepolymer to the polyamide prepolymer is 1-1.5:1; The molar ratio of the isocyanate to the polyol is 1-1.3:1; The molar ratio of the caprolactam to the adipic acid is 3-10:1; The process parameters of the heat drawing include: a drawing multiple of 1.5-4 times, a heat setting temperature of 80-120° C., and heat setting methods including pre-setting, mid-setting, and post-setting.

2. The process for preparing a highly elastic textile fiber according to claim 1, characterized in that: The polyol is selected from one of polyether glycol, polypropylene glycol, polycaprolactone glycol, polytetramethylene glycol, and hydroxy-terminated polydimethylsiloxane.

3. The process for preparing a highly elastic textile fiber according to claim 1, characterized in that: The isocyanate is selected from toluene diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, and terephthalylidene diisocyanate.

4. The process for preparing a highly elastic textile fiber according to claim 1, characterized in that: The chain extender is selected from one of butanediol, 2,2-dimethylolpropionic acid, 1,6-hexanediol and trimethylolpropane.

5. The process for preparing a highly elastic textile fiber according to claim 1, characterized in that: The modifier is selected from one of nano zinc oxide, nano silver oxide and trimethylammonium chloride acetylhydrazine.

6. The process for preparing a highly elastic textile fiber according to claim 1, characterized in that: The preparation of the polyurethane prepolymer comprises the following steps: Drying isocyanate and polyol in a vacuum drying oven at 80° C. for 2 hours to obtain a dry raw material; adding the polyol and the isocyanate into a flask and dissolving them in DMF to obtain a dissolving system; heating the dissolving system to 50° C., adding dibutyltin dilaurate and reacting for 3 hours to obtain a reaction system; adding a chain extender to the reaction system, and carrying out a chain extension reaction at 50-80° C. for 2 hours to obtain a polyurethane prepolymer; the molar ratio of the reaction system to the chain extender is 1:1-2.

7. The process for preparing a highly elastic textile fiber according to claim 1, characterized in that: The preparation of the polyamide prepolymer comprises the following steps: Caprolactam, deionized water and adipic acid were put into a reactor, the reactor was sealed with nitrogen, and the reaction was stirred at 100 rpm for 2 hours at 230° C. to obtain a reaction liquid; the reaction liquid was cooled and depressurized, and vacuumed for 5 minutes to remove moisture to obtain a polyamide prepolymer.

8. The process for preparing a highly elastic textile fiber according to claim 1, characterized in that: The preparation of the modified diatomite masterbatch comprises the following steps: Weigh diatomaceous earth and add it into a muffle furnace, calcine it at 450° C. for 2 h to obtain porous diatomaceous earth; add the porous diatomaceous earth into a ball mill for wet ultrafine grinding to make its average particle size reach the micron level to obtain ground diatomaceous earth; add the ground diatomaceous earth into 5 ml of sodium hydroxide solution, add a modifier, stir for 2 h at 200 r / min, centrifuge, sieve, and vacuum dry at 100° C. for 2 h to obtain modified diatomaceous earth masterbatch.

9. The process for preparing a highly elastic textile fiber according to claim 1, characterized in that: During the preparation of the modified diatomite masterbatch, the modifier accounts for 5%-15% of the mass of the diatomite.

10. A highly elastic textile fiber, characterized in that: The high elastic textile fiber comprises the polyurethane prepolymer, the polyamide prepolymer, and the modified diatomaceous earth masterbatch; the high elastic textile fiber is prepared by the preparation method according to any one of claims 1 to 9; the polyamide-polyurethane elastomer slice T in the high elastic textile fiber 5% 358℃, T 95% is 484°C; the breaking strength of the high-elastic textile fiber is 7.2cN / dtex, and the breaking elongation is 85.4%; the elastic recovery rate of the high-elastic spun fiber at a fixed elongation of 10% is 99.6%; the moisture regain of the high-elastic spun fiber at constant temperature and humidity for 48 hours is 8.58%; the Staphylococcus aureus inhibition rate of the high-elastic spun fiber is 99.6%, and the Escherichia coli inhibition rate is 99.5%.

Citation Information

Patent Citations

  • Melt-reaction preparation method of nylon polyurethane elastomer

    CN104558513A

  • Reactive dyes can easily dye spandex and their preparation methods

    CN113337916B

  • Antibacterial moisture-transfer chinlon 6 and preparation method thereof

    CN102677215A

  • Polyurethane-nylon 6 block copolymer, preparation method thereof and polyurethane-nylon 6 elastic fiber

    CN112127007A

Cited By

  • Breathable dustproof wall cloth and preparation method thereof

    CN120042072A

  • Elastic wear-resistant linen fabric and preparation method thereof

    CN120330939A

  • Self-adaptive radiation refrigeration fiber, preparation method thereof and application of self-adaptive radiation refrigeration fiber in textiles

    CN120844228A